2019
DOI: 10.1177/1024529419872171
|View full text |Cite
|
Sign up to set email alerts
|

Foreign bond investors and market discipline

Abstract: This article scrutinizes the impact of foreign bond ownership on market discipline, that is the mutual responsiveness of financial markets and sovereign borrowers. The empirical investigation covers 12 advanced economies during the Great Moderation (1981–2008). This article finds no evidence that foreign bond investors affect the sensitivity of bond spreads to fiscal policy. Reversely, results show that government responsiveness to market pressure is contingent on the make-up of its investor base. Bond spreads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 88 publications
0
9
0
1
Order By: Relevance
“…The yield spread is assumed to be a debt holder's reaction to the risk taken by banks. The relationship between the spread of yield and bank risks can indicate the existence of market discipline from debt holders' perspective, based on the evidence in foreign bond investors (Rommerskirchen, 2020), bondholders (Morrison and Walther, 2020), equity holders (Morrison and Walther, 2020) and depositors (Hou et al, 2016). In the context of Islamic banking, Aysan et al (2017) stated that the profit and loss sharing framework may contribute to market discipline.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield spread is assumed to be a debt holder's reaction to the risk taken by banks. The relationship between the spread of yield and bank risks can indicate the existence of market discipline from debt holders' perspective, based on the evidence in foreign bond investors (Rommerskirchen, 2020), bondholders (Morrison and Walther, 2020), equity holders (Morrison and Walther, 2020) and depositors (Hou et al, 2016). In the context of Islamic banking, Aysan et al (2017) stated that the profit and loss sharing framework may contribute to market discipline.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the market discipline in the context of withdrawal behavior in this study was examined using a behavioral financial approach. The other previous studies used some indicators reflecting the bank's risk, which were indicated in the financial statement and then related the risk to stock return (Morrison and Walther, 2020), bond spread (Morrison and Walther, 2020;Rommerskirchen, 2020) and deposit growth (Calomiris and Jaremski, 2019;Hou et al, 2016;Ioannidou and De Dreu, 2019). However, traditional finance theory cannot capture how financial decisions are made.…”
Section: Introductionmentioning
confidence: 99%
“…115. Ballard-Rosa 2016, 2020 partisanship are not systematically associated with the currency composition of government bonds, this measurement error will primarily serve to attenuate any true effect. Indeed, it is difficult to come up with a reason that such partisan codings would be likely to lead to directional bias in our primary estimates regarding proportions of domestic-currency denomination.…”
Section: Subset On Regime Typementioning
confidence: 99%
“…Chwieroth 2009Datz 2008. On the implications of variation in the investor base for fiscal consolidation, see Rommerskirchen 2020. 14.…”
Section: Trends In Developing-country Sovereign Debtmentioning
confidence: 99%
“…From being virtually isolated 20 years ago, portfolio investment that flowed into China increased unprecedentedly post-GFC (Figure 1). In neoliberal capital markets which are based on the principle of free capital movements, international investors’ ability to withdraw funds serves as disciplinary mechanism (Bortz and Kaltenbrunner, 2018; Rommerskirchen, 2020). The GFO is self-reinforcing.…”
Section: Integrating Into Global Finance: Resisting Neoliberal Capital Marketsmentioning
confidence: 99%